2013
DOI: 10.1007/s00464-012-2780-8
|View full text |Cite
|
Sign up to set email alerts
|

Robotic single-site hysterectomy: feasibility, learning curve and surgical outcome

Abstract: This series, identifying two different phases of the learning curve and suggesting that the initial learning phase for the procedure can be achieved after six cases, confirms the feasibility and safety of a robotic approach for single-site hysterectomy. However, the limits of this study mainly rely on the limited casuistic and short follow-up, although the preliminary results appear promising. Larger series and prospective studies comparing R-SSH hysterectomy with standard robotic multiport hysterectomy are ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 14 publications
3
50
0
Order By: Relevance
“…24 Food and Drug Administration approval for R-LESS hysterectomy and adnexal surgery was granted in 2013, and preliminary case reports for gynecological procedures suggest favorable surgical outcomes. [25][26][27][28][29][30] Furthermore, with regard to gynecological oncology procedures, Escobar et al 27 demonstrated feasibility with the R-LESS platform in the cadaveric model, and a small case control study of endometrial cancer patients who underwent LESS or R-LESS demonstrated similar operative outcomes between the 2 cohorts. 29 In the current prospective pilot study, a variety of gynecological procedures were performed in women with a median BMI of 28.2 kg/m 2 .…”
Section: Gynecology Researchmentioning
confidence: 92%
“…24 Food and Drug Administration approval for R-LESS hysterectomy and adnexal surgery was granted in 2013, and preliminary case reports for gynecological procedures suggest favorable surgical outcomes. [25][26][27][28][29][30] Furthermore, with regard to gynecological oncology procedures, Escobar et al 27 demonstrated feasibility with the R-LESS platform in the cadaveric model, and a small case control study of endometrial cancer patients who underwent LESS or R-LESS demonstrated similar operative outcomes between the 2 cohorts. 29 In the current prospective pilot study, a variety of gynecological procedures were performed in women with a median BMI of 28.2 kg/m 2 .…”
Section: Gynecology Researchmentioning
confidence: 92%
“…Most of these studies were retrospective and designed as feasibility studies, in which the number of patients was low and objective pain assessment by use of validated scales was not performed systematically [3,4,5]. …”
Section: Resultsmentioning
confidence: 99%
“…In gynecology today, almost all procedures can be performed endoscopically. Recently, a new method, single-site surgery was introduced in the field of minimally invasive surgery and initial reports have discussed the feasibility of this technique [3,7,8,9]. Since the introduction of robotic surgery, laparoendoscopic single-site surgery has been integrated with robotics, and two means of single-site endoscopic surgery have emerged.…”
Section: Discussionmentioning
confidence: 99%
“…However, the robotic system required an increased number and size of ports. In accordance with a minimally invasive vision, LESS and robotic systems have been integrated, and single-site robotic surgery in gynecological practice has been reported [7,8,9]. The da Vinci Single-Site robotic surgery platform (Intuitive, Sunnyvale, CA, USA) was designed for this technique.…”
Section: Introductionmentioning
confidence: 99%